2019
DOI: 10.2147/hiv.s229531
|View full text |Cite
|
Sign up to set email alerts
|

<p>Opportunistic Respiratory Infections in HIV Patients Attending Sukraraj Tropical and Infectious Diseases Hospital in Kathmandu, Nepal</p>

Abstract: Introduction: Opportunistic bacterial and fungal infections are the major cause of morbidity and mortality among immune suppressed HIV-positive patients. The main objective of this study was to determine bacterial and fungal organisms causing respiratory infections and their susceptibility to commonly prescribed antimicrobials among HIV patients attending a tertiary infectious disease hospital in Kathmandu. Methods: Sputum samples were collected from the HIV-positive patients attending Sukraraj Tropical and In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
3
17
1
Order By: Relevance
“…In this study, Candida albicans was the major species isolated from HIV-positive patients with oropharyngeal candidiasis. The findings of our study are consistent with the previous studies reported from Nepal, 18,24,59 and India. 40,60 The prevalence of oral candidiasis in HIVinfected individuals varies with the environment, although Candida albicans remains generally the most implicated.…”
Section: Types Of Candida Species Biofilm Producerssupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, Candida albicans was the major species isolated from HIV-positive patients with oropharyngeal candidiasis. The findings of our study are consistent with the previous studies reported from Nepal, 18,24,59 and India. 40,60 The prevalence of oral candidiasis in HIVinfected individuals varies with the environment, although Candida albicans remains generally the most implicated.…”
Section: Types Of Candida Species Biofilm Producerssupporting
confidence: 93%
“…In our study, one third of HIVpositive patients had CD4+ cells below 200 cells/µL and there was a significant association between oral candidiasis and low CD4+ count. The findings are consistent with the past studies conducted in STIDH, Kathmandu, 18 New Delhi, India, 50 Italy, 51 Awka, Nigeria, 52 and Nigeria. 53 However, the findings of our study were in contrast with other studies reported from India 40 and Brazil.…”
Section: Sociodemographic Factors Clinical Factors and Candida Colonizationsupporting
confidence: 92%
See 3 more Smart Citations